Once More Unto The Breach: Some Thoughts on the Future of the EEZ - Rosiers, Guy Des (Indonesian Journal of International Law, 2011)
By public international law standards, the Exclusive Economic Zone (EEZ) maintains a relative newcomer, the product of State practice following the end of the Second World War and multilateral negotiations culminating with the entry into force, in November 1994, of the 1982 United Nations Convention of the Law of the Sea, In defining the EEZ, the Convention has created a sui generis legal regime over vast areas that were previously part of the high seas. Neither Grotian nor Seldenian in spirit, the EEZ regime forgoes the absolute language of territory and sovereignty in favor of discrete sets of rights and obligations, leaving many legal and practical questions unanswered. The modest aim of this paper is to highlight a few of the gray areas that have since emerged, by reference to recent State practice,